Highlighting an Advanced Practice Fellowship for Leadership Transition. (March 2023) - Bugos, Kelly; Mansour, Salma; Stringer, Meredith A.; Kuriakose, Clair
Abstract : As the advanced practice provider (APP) workforce continues to rapidly grow in healthcare, there is a greater need for APP leadership positions. Often, these positions are organically designated to the best clinicians on the team, who may not have leadership experience. Stanford Health Care Center for Advanced Practice embarked on formalized leadership training using a newly developed administration specialty within the APP Fellowship Program to support new leader transition.